A STUDY OF LOCAL AGRICULTURAL MATERIALS AS ALTERNATIVES TO RUBBER TREE SAWDUST FOR MUSHROOM SPAWN SUBSTRATE PRODUCTION - Phungbunhan, Karun; Intaravicha, Nuttakorn (Life Sciences and Environment Journal, 2024)
This research aimed to evaluate the potential of local agricultural materials for use in mushroom spawn block production. The study was conducted in three phases. First, the components of mushroom spawn blocks and available agricultural materials were explored through in-depth interviews with community enterprise leaders, group representatives, and agricultural product buyers in the study area. Second, the selection of suitable agricultural materials to replace rubber tree sawdust was carried out using a Multiple-Criteria Decision Analysis (MCDA) approach. Third, the proportions of the selected agricultural materials were analyzed through proximate analysis to assess their feasibility for spawn block formulation. The results revealed that rubber tree sawdust is the primary component currently used in spawn block production. Local agricultural materials found in the study area included rice husk, rice straw, corn cobs, and sugarcane filter cake. Among these, rice husk and rice straw were identified as the most suitable for partial replacement of rubber tree sawdust. The optimal formulation was 80% rubber tree sawdust and 20% rice husk, which demonstrated a promising potential for practical application in mushroom cultivation.